Nanotechnology and picotechnology to increase tissue growth: a summary of in vivo studies - Alpaslan E (Dove Medical Press, 2014)
Ece Alpaslan,1 Thomas J Webster1,21Department of Chemical Engineering, College of Engineering, Northeastern University, Boston, MA, USA; 2Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi ArabiaAbstract: The aim of tissue engineering is to develop functional substitutes for damaged tissues or malfunctioning organs. Since only nanomaterials can mimic the surface properties (ie, roughness) of natural tissues and have tunable properties (such as mechanical, magnetic, electrical, optical, and other properties), they are good candidates for increasing tissue growth, minimizing inflammation, and inhibiting infection. Recently, the use of nanomaterials in various tissue engineering applications has demonstrated improved tissue growth compared to what has been achieved until today with our conventional micron structured materials. This short report paper will summarize some of the more relevant advancements nanomaterials have made in regenerative medicine, specifically improving bone and bladder tissue growth. Moreover, this short report paper will also address the continued potential risks and toxicity concerns, which need to be accurately addressed by the use of nanomaterials. Lastly, this paper will emphasize a new field, picotechnology, in which researchers are altering electron distributions around atoms to promote surface energy to achieve similar increased tissue growth, decreased inflammation, and inhibited infection without potential nanomaterial toxicity concerns.Keywords: nanomaterials, tissue engineering, toxicity